Odpowiedzi

Najlepsza Odpowiedź!
2009-12-15T23:19:15+01:00
A) 3(2x-1)-5(x-3)+6(3x-4)=83
6x-3-5x+15+18x-24=83
19x=83+12
19x=95
x=5

B) 0,2x+0,5x+5(5x-1)-2,7x=6,5
0,2x+0,5x+25x-5-2,7x=6,5
23x=11,5
x=1/2
2009-12-15T23:21:37+01:00
A. 3(2x-1)-5(x-3)+6(3x-4)=83
6x - 3 - 5x + 15 + 18x - 24 = 83
6x - 5x + 18x = 83 + 3 - 15 + 24
19x = 95 /:19
x = 5
B. 0,2x+0,5x+5(5x-1)-2,7x=6,5
0,2x + 0,5x + 25x - 5 - 2,7x = 6,5
0,2x + 0,5x + 25x - 2,7x = 6,5 + 5
23x = 11,5 /:23
x = 0,5
2009-12-15T23:23:51+01:00
(A)
3(2x-1)-5(x-3)+6(3x-4)=83
6x-3-5x+15+18x-24=83
19x-12=83
19x=83+12
19x=95 /:19
x=5
(B)
0,2x+0,5x+5(5x-1)-2,7x=6,5
0,7x+25x-5-2,7x=6,5
23x-5=6,5
23x=6,5+5
23x=11,5 /:23
x=0,5
1 5 1